Grip strength measured by manual muscle testing lacks diagnostic accuracy - Bohannon, R. W. (Isokinetics and Exercise Science, 2018)
BACKGROUND: The diagnostic accuracy of manual muscle testing (MMT) has been examined- but not for grip strength. OBJECTIVE: Determine the diagnostic accuracy of MMT relative to grip dynamometry for identifying patients with weak grip strength. METHODS: This study involved the secondary analysis of grip strength data obtained from 61 patients managed in a home care setting. The concordance between weakness identified using MMT and grip dynamometry was examined. RESULTS: The agreement between MMT and dynamometry was about 70%. Kappa suggested fair agreement beyond chance. Sensitivity and specificity ranged from 66.7 to 73.4 percent. CONCLUSIONS: Grip strength measured using MMT lacks sufficient diagnostic accuracy to advocate its use - at least with patients seen in a home setting.